THE EVALUATION OF INVESTMENT PROJECTS FOR IMPLEMENTING CLOUD TECHNOLOGY - Alexander Sergeevich Volozhenin (Современная наука и инновации, 2022)
The article presents an overview of information on the features, opportunities and prospects of investing in cloud computing in construction. The general analysis of cloud computing level on the world market is carried out, the main problems of cloud technologies promotion to the Russian market are revealed, and the positive aspects of work in the sphere of these technologies are presented. Among other things, the paper presents an example of the calculation of the interest rate used to convert future cash flows into a single value of the current value, estimated the net present value of cash flows of investment in the implementation of cloud-based technologies in the construction company, to make estimates of the effectiveness of invested funds, taking into account the main risks. The results determine the prospects for the development and application of cloud computing in construction.